God in Motion : A Critical Exploration of the Open Theism Debate - Schmid, Manuel, 1976- (Book collections on Project MUSE., 2021)
"Provides an assessment of the roots, methods, claims, and significance of Open Theism in North American evangelicalism, in conversation with contemporary German theology"--